Protocol, Potentials, and Limitations of Ancient Teeth 3D Printing - Alfonso-Durruty, Marta; Morello Repetto, Flavia; Misarti, Nicole; Vilar, Miguel G.; Headley, Dustin (My University, 2018)
Bioarchaeological analyses of teeth rely traditionally on noninvasive methods that reveal essential information about past individuals and populations. Methodological developments have revolutionized the discipline, but their application is commonly invasive and destructive. The resulting loss of material and information can be buffered through 3D technology applications. Although useful, it is essential that we carefully assess the reliability of these methods, in order to understand what data are preserved and which ones are lost through their application. This study offers a protocol for the implementation of 3D technology in the fabrication of ancient teeth analogs. Analog accuracy was assessed by comparing metric and non-metric traits between the originals and their respective analogs. Results showed that metric traits preserved well, but the preservation of non-metric traits was partially hindered.
Keywords: digital bioarchaeology; teeth analogs; 3d scanning; 3d printing; dental anthropology